SYNTHESIS OF SPECTRAL-TIME PARAMETERS OF THE MODULES BLOCK SPEECH RECOGNITION IN AUTOMATED CONTROL SYSTEM - Karpov, O. M.; Savenkova, O. O. (Science and Transport Progress, 2007)
Algorithm of segment-syllabic synthesis of time-spectrum parameters for the model of speech recognition block is introduced.